2019
DOI: 10.1007/s10092-019-0327-2
|View full text |Cite
|
Sign up to set email alerts
|

A posteriori error estimates for the monodomain model in cardiac electrophysiology

Abstract: We consider the monodomain model, a system of a parabolic semilinear reaction-diffusion equation coupled with a nonlinear ordinary differential equation, arising from the (simplified) mathematical description of the electrical activity of the heart. We derive a posteriori error estimators accounting for different sources of error (space/time discretization and linearization). We prove reliability and efficiency (this latter under a suitable assumption) of the error indicators. Finally, numerical experiments as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…In general, a good agreement is noted. It is observed that in accordance with the previous numerical estimation [35] and experimental observation [19],…”
Section: Propagation Of Transmembrane Potentialsupporting
confidence: 91%
See 2 more Smart Citations
“…In general, a good agreement is noted. It is observed that in accordance with the previous numerical estimation [35] and experimental observation [19],…”
Section: Propagation Of Transmembrane Potentialsupporting
confidence: 91%
“…Here, we consider the Aliev-Panfilow model with the constant parameters given in Table 1. Figure 7 reports the predicted evolution profile of the transmembrane potential at point (0.3, 0.7), and the comparison with those from Ratti and Verani [35]. In general, a good agreement is noted.…”
Section: Propagation Of Transmembrane Potentialmentioning
confidence: 62%
See 1 more Smart Citation
“…Finally, the detection of arbitrarily large ischemic regions can be tackled, exploiting an analogous strategy as the one adopted in [6] (possibly reducing the computational effort by employing an adaptive solver of the monodomain system, as proposed in [32]).…”
Section: Discussionmentioning
confidence: 99%
“…This leads to solve a nonlinear problem at each timestep, which is performed via a Newton iterative algorithm. More details on the solver can be found in [32], where a thorough convergence analysis is performed.…”
Section: Finite Element Approximationmentioning
confidence: 99%